(untitled) (Research, Society and Development, 2022)
The use of films, coatings or edible films applied to products is of growing importance in the food industry. Alginate is a widely used polysaccharide and rosemary and oregano oils have been applied as antimicrobial and antioxidant agents. The resistance of these films and the mass transfer through them are important parameters and must be studied. Thus, this work aimed to characterize an edible covering based on alginate and essential oils (rosemary and oregano). It can be seen that the addition of oils did not influence (p<0.05) the thickness and water solubility of the samples. The control sample (without essential oils) showed higher humidity (approximately 37 % higher) and lower water vapor permeability (65 % in average). It can also be concluded that the rosemary coating showed higher tensile strength and elongation. Thus, it can be concluded that the addition of essential oils in edible coverings made them more resistant when compared to the sample without this addition, indicating that they have potential for application in food.